Competences in health network management: A textbook for training regional health network managers - Yvonne Behrens; Sandra Macher; Zsófia Kollányi; Isabel Morales Moreno; Velko Iltchev; Piotr Romaniuk; Klaudia Alcer; Krzystof Kaczmarek; Katarzyna Brukało; Catalina Morales Hernández; José Palacios Ramírez; Roberto Ferrándiz Gomis; et al. (MA Akademie Verlags- und Druck-Gesellschaft mbH, 2022)
[Introduction:] Health regions are clusters that unite regional competences around the topic of health (Behrens, Movia 2020). In order to manage health regions successfully, interdisciplinary competences are needed. These competences were identified in the Competences in Health Network Management (Com.HeNet) project and transferred into teaching modules. The teaching modules cover the areas of health science, project management and information technology. The target group of this textbook is people who are training for the management of health regions. Teaching staff in this as well as in related fields can successfully use the book as a whole or its individual teaching chapters. This book can be used internationally as it is a European module. If necessary, national specifics have to be adapted individually. Determining these is also the content of this book. This book was developed in an international consortium and is based on international scientific cooperation. We would like to thank all the supporters of the project. The Textbook Competences first embeds the work in the Com.HeNet project. It then provides an insight into the structure and management of health regions. Finally, theoretical contents from the following six teaching units are dealt with in detail: Health and society - theoretical background, Health Needs Assessment, Promoting the Network, Project Management, Strategic Management and Planning, Database Systems, Data Protection and Security. Learning objectives are defined for each chapter. The learning success of the individual chapters can be checked by means of the control questions. Finally, a conclusion is given. This book was positively evaluated by international students.
Keywords: 360; Health Management; Regional Health Network Management; Education; Competences in Health Network Management; Health regions; Project Management; Public Health; Health Care Management; Network